MRI visibility of the anterolateral ligament and the deep structures of the iliotibial tract - Liebensteiner, Michael (J Exp Orthop, 2020)
PURPOSE: The visualization of potentially injured anatomical structures is crucial. Lately the anterolateral ligament (ALL) and the deep structures of the iliotibial tract (ITT) have been of increased clinical interest because of their role as important lateral stabilizers of the knee. The aim of this study was to assess the visibility of the ALL and the deep structures of the ITT using MRI. Good intra- and inter-observer reproducibility was hypothesized. METHODS: Knee MRI data from patients without ligamentous lesions were retrospectively analyzed by two radiologists at two time points using axial and coronal sequences. The visibility of the different parts of the ALL (femoral, meniscal and tibial part) and of the deep ITT, namely the deep attachments of the ITT to the distal femur and capsulo-osseous layer of the ITT, were determined on a binary (yes/no) basis. RESULTS: Seventy-one cases (42 men, 29 women) were studied. Inter-observer agreement was high. Cohen’s kappa was 0.97 for the tibial part of the ALL and 0.76 for the femoral part. For the deep attachments of the ITT to the distal femur Cohen’s kappa was 0.94. For each of the investigated parameters absolute agreement between the observers was at least 88%. Regarding intra-observer agreement Cohen’s kappa was 0.62 for the femoral part of the ALL and 0.85 for the tibial part of the ALL. For the deep attachments of the ITT to the distal femur Cohen’s kappa was 0.94. For each investigated parameter absolute agreement between the two time points was at least 83%. CONCLUSIONS: The presence of the anterolateral structures of the knee can be determined with substantial inter- and intra-observer agreement using MRI examination. This is applicable for both the ALL and the deep ITT. LEVEL OF EVIDENCE: Diagnostic study – Level III.